The Current Role of Androgen Deprivation in Patients Undergoing Dose-Escalated External Beam Radiation Therapy for Clinically Localized Prostate Cancer - Michael J. Smith; Naveed H. Akhtar; Scott T. Tagawa (Prostate Cancer)
Purpose. To review existing literature on the role of androgen deprivation therapy (ADT) with dose escalated radiation therapy. Methods and Materials. A PubMed search was undertaken to identify relevant articles. Results. Multiple recent studies were identified examining the role of ADT in the current era of radiation dose-escalation. Among the reviewed studies, varying radiation doses and techniques, ADT regimens, and patient selection criteria were utilized. Conflicting results were reported, with some studies demonstrating a benefit of delivering a higher radiation dose with ADT. Other studies failed to show significant benefits with the addition of ADT to dose-escalated RT. Conclusions. The benefit of adding ADT to dose-escalated RT is still uncertain. Prospective randomized trials, several of which are ongoing, are necessary to more adequately examine this issue. In the interim, physicians and patients should continue to utilize the existing data to weigh the risks and benefits of each approach to therapy.